If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1y = 11 Solving 5x + -1y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 5x + -1y + y = 11 + y Combine like terms: -1y + y = 0 5x + 0 = 11 + y 5x = 11 + y Divide each side by '5'. x = 2.2 + 0.2y Simplifying x = 2.2 + 0.2y
| w-9.91=12.6 | | x/3-1=7 | | 3x^2+23x-5.7=0 | | 2y-6=6(y-3) | | f(x)=3x-7 | | 15=-1K+8 | | 6n-14=4n+20 | | x+x+4=9 | | n3/2=125 | | 3/7x-11=-4/7x | | 4/x-3 | | -6=y/5-9 | | -1B+2=.5 | | -5*30-5y=25 | | 3y+9=8y-16 | | 3x+(-5)=7 | | -6+4n=2n+6 | | -50-6= | | -5*25-5y=25 | | 5x+30=8x | | 4(k-5)+6(k+5)=30 | | 19=a+h | | (4/x)+(x-3/2x+3)=3 | | 9/x=51/34 | | 2(y^2-2y-4)=-y^2+y | | x^2+27=-9 | | 19=2(4a) | | 2x+31+3x=-19 | | 35+2y=10 | | 3a-8a-4a=21 | | ((2x-7)/7)14 | | (8/x)-(x/18)=0 |